2018
DOI: 10.4314/as.v17i2.4
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of commercial cultivars of okra, pepper, and tomato to cucumber mosaic virus disease

Abstract: Okra (Abelmoschus esculentus), pepper (Capsicum spp.) and tomato (Solanum lycopersicum) are rich sources of minerals and vitamins required by humans for normal growth and development. However, the productivity of these vegetables is seriously constrained by Cucumber mosaic virus (CMV) disease. To date, adoption of resistant cultivars is the most effective, ecologically sound and sustainable management strategy against the disease. Therefore, selected cultivars of okra (Clemson Spineless, Ex Bassawa-2 and NHAe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
1
0
0
Order By: Relevance
“…Essoumtem cultivar was tolerant to the virus infection as plant height reduction was insignificant when compared to the control. Similar observations were made by Salaudeen et al 24 , who reported insignificant differences in plant height between uninoculated okra plants and okra plants infected with the Cassava mosaic virus (CMV) in Ex-Bassawa-2, Cayenne and Roma Savanna cultivars in a screen house experiment.…”
Section: Discussionsupporting
confidence: 82%
“…Essoumtem cultivar was tolerant to the virus infection as plant height reduction was insignificant when compared to the control. Similar observations were made by Salaudeen et al 24 , who reported insignificant differences in plant height between uninoculated okra plants and okra plants infected with the Cassava mosaic virus (CMV) in Ex-Bassawa-2, Cayenne and Roma Savanna cultivars in a screen house experiment.…”
Section: Discussionsupporting
confidence: 82%